Data communications and networking - Forouzan, Behrouz A. (New York : McGraw Hill Education, 2013)
Helps students to understand the basics of data communications and networking, and the protocols used in the Internet in particular by using the protocol layering of the Internet and TCP/IP protocol suite.
Part I: Overview Chapter 1 Introduction Chapter 2 Network Models Part 2: Physical Layer Chapter 3 Introduction to Physical Layer Chapter 4 Digital Transmission Chapter 5 Analog Transmission Chapter 6 Bandwidth Utilization: Multiplexing and Spreading Chapter 7 Transmission Media Chapter 8 Switching Part 3: Data Link Layer Chapter 9 Introduction to Data-Link Layer Chapter 10 Error Detection and Correction Chapter 11 Data Link Control (DLC) Chapter 12 Media Access Control (MAC) Chapter 13 Wired LANs: Ethernet Chapter 14 Other Wired Networks Chapter 15 Wireless LANs Chapter 16 Other Wireless Networks Chapter 17 Connecting Devices and Virtual LANs Part 4: Network Layer Chapter 18 Introduction to Network Layer Chapter 19 Network-Layer Protocols Chapter 20 Unicast Routing Chapter 21 Multicast Routing Chapter 22 Next Generation IP Part 5: Transport Layer Chapter 23 Introduction to Transport Layer Chapter 24 Internet Transport-Layer Protocols Part 6: Application Layer Chapter 25 Introduction to Application Layer Chapter 26 Standard Client-Server Protocols Chapter 27 Network Management Chapter 28 Multimedia Chapter 29 Peer-to-Peer Paradigm Part 7: Topics Related to All Layers Chapter 30 Quality of Service Chapter 31 Cryptography and Network Security Chapter 32 Internet Security
Includes bibliographical references.
Keywords: DATA TRANSMISSION SYSTEMS